Neuron-derived exosomes mediate sevoflurane-induced neurotoxicity in neonatal mice via transferring lncRNA Gas5 and promoting M1 polarization of microglia - Xu Li-li; Xie Jia-qian; Shen Jian-jun; Ying Mei-dan; Chen Xin-zhong (Acta Pharmacologica Sinica, 2024)
Sevoflurane exposure during rapid brain development induces neuronal apoptosis and causes memory and cognitive deficits in neonatal mice. Exosomes that transfer genetic materials including long non-coding RNAs (lncRNAs) between cells play a critical role in intercellular communication. However, the lncRNAs found in exosomes derived from neurons treated with sevoflurane and their potential role in promoting neurotoxicity remain unknown. In this study, we investigated the role of cross-talk of newborn mouse neurons with microglial cells in sevoflurane-induced neurotoxicity. Mouse hippocampal neuronal HT22 cells were exposed to sevoflurane, and then co-cultured with BV2 microglial cells. We showed that sevoflurane treatment markedly increased the expression of the lncRNA growth arrest-specific 5 (Gas5) in neuron-derived extracellular vesicles, which inhibited neuronal proliferation and induced neuronal apoptosis by promoting M1 polarization of microglia and the release of inflammatory cytokines. We further revealed that the exosomal lncRNA Gas5 significantly upregulated Foxo3 as a competitive endogenous RNA of miR-212-3p in BV2 cells, and activated the NF-κB pathway to promote M1 microglial polarization and the secretion of inflammatory cytokines, thereby exacerbating neuronal damage. In neonatal mice, intracranial injection of the exosomes derived from sevoflurane-treated neurons into the bilateral hippocampi significantly increased the proportion of M1 microglia, inhibited neuronal proliferation and promoted apoptosis, ultimately leading to neurotoxicity. Similar results were observed in vitro in BV2 cells treated with the CM from HT22 cells after sevoflurane exposure. We conclude that sevoflurane induces the transfer of lncRNA Gas5-containing exosomes from neurons, which in turn regulates the M1 polarization of microglia and contributes to neurotoxicity. Thus, modulating the expression of lncRNA Gas5 or the secretion of exosomes could be a strategy for addressing sevoflurane-induced neurotoxicity.